983 Temporal Artery Biopsy - Bringing About a Much-Needed Change. (19th August 2022) - Krishnakumar, N; Barnes, R
Abstract: Aim: Looking into the process for sending a referral for a Temporal Artery Biopsy (TAB) and the causes of delays for the procedure at a local DGH. Method: A retrospective review of all the TAB referrals sent and the time from referral to date of procedure over the past year done from11/2020 to 11/2021 was done. Specifically noticed points included urgency, side, time till date of procedure. Results: Out of the 47 procedures done, 36% of the referrals were sent and about 64% were sent as urgent all of which were sent as emails to secretaries. The average time from referral to date of procedure was about 16 days, however urgent inpatient referrals with severe active symptoms were done by the 6th or 7th day from referral. About 7% of the referrals did not even include site required and 10% did not specify date since use of steroids. About 10% of the patients found to have not understood the procedure completely and its necessity which also contributed to delays. Conclusions: This study found that a significant proportion of the TAB referrals were incomplete, that there was a need to re-review the entire patient information thus ending up in delays. A consensus to create a new referral system specifically for TAB which includes all the relevant data for the surgeon and a new patient leaflet including a consent form which has been discussed and is in the stage of implementation for streamlining the process, improving patient experience, and causing positive impact on overall department functioning.